PERAN SBS DALAM MENCIPTAKAN VARIETY SHOW “RUNNING MAN” SEBAGAI INSTRUMENT SOFT POWER KOREA SELATAN - Hotimah, Husnul; Resen, Putu Titah Kawitri; dewi, Putu Ratih Kumala (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2025)
This study aims to analyze how Seoul Broadcasting System (SBS) packages the content of Running Man to serve as an instrument of South Korea’s soft power. Running Man is a popular variety show that has been broadcast for over 14 years, making it one of Korea’s longest-running programs. Each episode incorporates Korean cultural elements, such as traditional food, traditional clothing, tourist destinations, and historical narratives. This research employs a qualitative method with content analysis to explore the cultural elements featured in the program and their impact on international audiences. The findings reveal that SBS consistently integrates various cultural elements into an engaging entertainment format, allowing Running Man to effectively introduce Korean culture to global audiences. Furthermore, the South Korean government actively supports this cultural promotion through location access and policy initiatives. This study highlights the role of broadcasting media in supporting cultural diplomacy through entertainment.